PERAN PROGRAM KHITOBAH EKSTRAKURIKULER KEAGAMAAN DALAM MENGEMBANGKAN KETERAMPILAN KOMUNIKASI SISWA DI MAN 1 CIANJUR - Wulandari, Fitri; Jenab, Siti (LPPM STAI Al-Azhary Cianjur, 2024)
The lack of understanding regarding communication skills theory, as well as the low level of communication skills practice, resulting in students not daring to speak in public, are the main reasons why the Religious Extracurricular program uses various efforts to help students develop their communication skills through the provided learning activities. This research aims to understand the Khitobah (Public Speaking) program of the Religious Extracurricular in developing communication skills, as well as the results and inhibiting factors of its implementation for students at MAN 1 Cianjur. This research uses a qualitative method that is descriptive and employs 3 data collection techniques: interviews, observation, and documentation. Based on the research results, the Khutbah program plays a significant role in developing students' communication skills at MAN 1 Cianjur, with the existing programs in Khutbah, namely the real dimension program and the digital dimension program, as well as a program from the Religious Extracurricular itself, the Syartudiniyah program. Thus, students can become skilled in delivering da'wah or speaking in public with the khutbah and general programs from this Religious Extracurricular program.